Use of Pleurotus eous Strain P-31 Spent Mushroom Compost (SMC) as Soil Conditioner on the Growth and Yield Performance of Capsicum annuum L. and Solanum lycopersicon L. Seedlings under Greenhouse Conditions in Ghana - Wiafe-Kwagyan M,; Odamtten G T, (Tropical Life Sciences Research, 2018)
The objective of this study was to investigate the influence of spent mushroom compost of Pleurotus eous strain P-31 on the growth and yield performance of pepper and tomato seedlings under greenhouse conditions. Sandy loam soil was combined with different percentages of SMC to obtain the following combinations (0, 5, 10, 15, 20, 25 and 30) %. Lower concentrations SMC5, SMC10 and SMC15 promoted vegetative growth (plant height, leaf area, chlorophyll content, number of leaves and axillary branches) of the two test plants. Tomato seedlings grown in SMC10 recorded the highest plant height (50.3 ± 7.2cm); leaf area (378.8 ± 1.2cm2); number of floral buds (51) and flowers (28) whereas SMC5 recorded the highest chlorophyll content 34.1 ± 0.9CCI though SMC15 recorded the highest number of leaves (8). Tomato seedlings grown in SMC30 produced both the maximum number of fruits (8) with corresponding high weight (34.2 ± 7.7g). Pepper seedlings grown in lower concentrations (SMC5–15) recorded the highest plant heights (29.8–30.8cm), chlorophyll content (20.3CCI) and leaf area (53.5–66.2 cm2). Although the different combinations of sandy loam soil and SMC did not significantly (p ? 0.05) affect the number of axillary branches developed; different combinations significantly (p ? 0.05) affected the number of floral bud, flower and fruit, weight of fruits formed and value of each of these increased with increasing percentage of SMC. Pepper seedlings grown on SMC30 recorded the maximum number of floral buds (32.0 ± 3.6), number of flowers (19.4 ± 1.3), number of fruits (10.8 ± 1.2) and weight of fruits (31.9 ± 3.4g). Tomato seedlings raised on SMC100 (spent mushroom compost only) and soil only did not significantly (p ? 0.05) differ from each other however, was statistically significant (p ? 0.05) from amended sandy loam soil by all criteria investigated. The study shows that SMC provide favourable soil conditioners for the cultivation of fruits, vegetables and foliage crops as it improved growth and yield of tomato and pepper seedlings.